Global Alfvén eigenmode scaling and suppression: experiment and theory. (29th June 2018) - Fredrickson, E.D.; Belova, E.V.; Gorelenkov, N.N.; Podestà, M.; Bell, R.E.; Crocker, N.A.; Diallo, A.; LeBlanc, B.P.
Abstract: The spherical tokamak NSTX has been upgraded to include a second neutral beam line, with three independent beam sources, and to be capable of higher toroidal fields and longer duration plasmas (Ono et al 2015 Nucl. Fusion 55 073007). In this paper we describe some of the initial observations of the affect that the higher field and the modified fast-ion distributions have had on the nature of the global Alfvén eigenmodes (GAE). We also report that the GAE excited through a Doppler-shifted ion cyclotron resonance (DCR) were suppressed in a large number of shots with the injection of a small amount of high pitch ( V || / V ) fast ions, consistent with the predictions of an analytic theory (Gorelenkov et al 2003 Nucl. Fusion 43 228). We show that the experimental scaling of the GAE frequency and toroidal mode numbers with toroidal field is qualitatively consistent with the predictions of the analytic theory, providing validation for the DCR model. The observed suppression of GAE has also been reproduced in simulations with the hybrid ideal stability code HYM (Belova et al 2017 Phys. Plasmas 24 042505).